Family income is associated with quality of life in patients with chronic kidney disease in the pre-dialysis phase: a cross sectional study. Issue 1 (December 2015) - Lemos, Camila; Rodrigues, Marcelo; Veiga, Joel
Abstract Background Chronic kidney disease (CKD) is a condition of high prevalence in the general population mainly due to hypertension and diabetes mellitus. It is often associated with a high prevalence of complications and worse quality of life. The main objective of this study is to evaluate quality of life (QOL) using the generic instrument SF-36 in patients with CKD in pre-dialysis and identify the possible influence of the degree of renal function, hemoglobin level, age, gender, family income and level of education on QOL. Methods A cross-sectional study was conducted and included 170 individuals (83 men) with a mean age of 57 ± 15 years who met the inclusion criteria and answered the SF-36. Laboratory tests and clinical and demographic data were obtained, and the glomerular filtration rate was estimated using the CKD-EPI formula. Results The degree of renal function did not influence QOL. Women had lower scores in functional capacity, physical aspects, pain, and mental health. Patients younger than 47 years old showed better QOL in the functional capacity; however, their QOL was worse in terms of social aspects. Subjects with an income higher than 5.1 times the minimum wage had better QOL in the functional capacity, pain, social, physical and emotional roles, and mental health. Hemoglobin levels and education did not globally influence QOL. Conclusion Gender and age influenced QOL, but family income was the most important factor affecting QOL (6 out of 8 domains investigated by SF-36) in this sample of 170 individuals with CKD in pre-dialysis. These findings suggest that many efforts should be made to reduce the effect of these factors on quality of life in patients with CKD and reinforce the need for longitudinal studies and intervention.